Pengembangan Media Pembelajaran Modul Interaktif Dengan Software Adobe Flash pada Mata Kuliah Matematika Ekonomi di Universitas Batanghari Jambi - Diliza Afrila; Ayu Yarmayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This reserach is aimed at identifying (1) the development process of interactive module learning media with Adobe Flash software in Economics Mathematics in Batanghari University Jambi, (2) The advisability of interactive module learning media Adobe Flash software in Economics Mathematics in Batanghari University based on material and media experts assessment, and (3) The advisability of interactive module learning media with Adobe Flash software in Economics Mathematics course in Batanghari University based on students assessment. This research uses Research and Development method. The subject of the research is one expert in Economics Mathematics course, one expert in media, and the students of Economics Education Study Program Faculty of Teachers Training and Education Batanghari University Jambi which cosist of 20 (twenty) people. Moreover, the object of this researh is the advisability of interactive module learning media which consists of 4 aspects, they are; content material, learning material, performance and presentation, and programming. The result of the research shows that (1) The development process of interactive module learning media with Adobe Flash software in Economics Mathematics in Batanghari University Jambi refers to the development model ADDIE which consists of 5 (five) steps, they are; Analysis, Design, Development, Implementation, and Evaluation, (2) The advisability of interactive module learning media with Adobe Flash software in Economics Mathematics Batanghari University Jambi based on Economics Mathematics course based on expert assessment falls into mean category 4,94. It prooves that this learning material can be efficiently used in Economics Mathematics learning process. Furthemore, based on media expert, the process falls into mean category 4,85. It means that this learning media can be efficiently used in Economics Mathematics learning process, and (3) The advisability of interactive module learning media with Adobe Flash software based on learning assessment in Economics Mathematics learning falls into mean category 4,25. It proves that this learning media can be efficiently used in Economics Mathematics learning process.